2022
DOI: 10.1002/chem.202201812
|View full text |Cite
|
Sign up to set email alerts
|

Effective Charge Carrier Utilization of BiVO4 for Solar Overall Water Splitting

Abstract: Solar energy-driven overall water splitting (OWS) is an attractive way for generating clean and renewable green hydrogen. One key challenge is the construction of OWS systems with high solar energy conversion efficiencies, in which how to manipulate photoexcited charge carriers to efficiently participate in the reaction is the top priority. In recent years, bismuth vanadate (BiVO 4 ) has emerged as one of the most promising materials for photo(electro)catalytic OWS and considerable progress has been achieved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…To quote a few: a rigorous characterization dataset with evidence of negligible impurities impeding the excellent process of photocatalysis, a comparison of catalysts in terms of quantum yield (QY) instead of turnover frequency (TOF), or reporting both the catalyst activity in terms of mass and surface area per unit. Among the reviews and studies encountered in the specific case of BiVO 4 , 15–21 we observed an excellent characterization procedure with deep scrutiny of the catalyst surface. The latter reveals the encouraging performance of the BiVO 4 particles (scheelite) designed for a given photoelectrode, with a systematic photocurrent density between 3 and 6 mA cm −2 , low resistance (below 10 Ω), and high purity of the designed material.…”
Section: Langmuir–blodgett Approach To Scale Up Photoelectrode: Case ...mentioning
confidence: 96%
See 1 more Smart Citation
“…To quote a few: a rigorous characterization dataset with evidence of negligible impurities impeding the excellent process of photocatalysis, a comparison of catalysts in terms of quantum yield (QY) instead of turnover frequency (TOF), or reporting both the catalyst activity in terms of mass and surface area per unit. Among the reviews and studies encountered in the specific case of BiVO 4 , 15–21 we observed an excellent characterization procedure with deep scrutiny of the catalyst surface. The latter reveals the encouraging performance of the BiVO 4 particles (scheelite) designed for a given photoelectrode, with a systematic photocurrent density between 3 and 6 mA cm −2 , low resistance (below 10 Ω), and high purity of the designed material.…”
Section: Langmuir–blodgett Approach To Scale Up Photoelectrode: Case ...mentioning
confidence: 96%
“…Recent advancements in the development of photoelectrocatalysts have focused on transition metal oxides, 13,14 particularly scheelite-type monoclinic BiVO 4 , sometimes completed by carbon moieties as cocatalysts (GO, MWCNT), owing to their advantages in scaling up photoelectrodes, such as an adapted band gap for solar absorption (2.4 eV (VIS)), efficient charge separation, and atomic element availability. [15][16][17][18][19][20][21] Although these compounds are still under study, ongoing research aims to validate their efficiency and long-term stability under real working conditions.…”
Section: Douglas Santos Monteiromentioning
confidence: 99%
“…Solar water splitting with the assistance of photocatalysts, i.e., direct conversion of solar energy into hydrogen energy, provides a promising route to solve the energy crisis. Bismuth vanadate (BiVO 4 ) has emerged as one of the most promising visible-light photoanode materials in recent years, due to an ideal bandgap (∼2.4 eV), a relatively high conduction band edge (0.02 V vs RHE), and a low bias voltage to achieve the reduction potential of water. However, the performance of BiVO 4 photocathodes is limited by low charge carrier mobility (∼0.04 cm 2 V –1 s –1 ) and rapid recombination of photogenerated electrons and holes, which make its actual catalytic efficiency lower than the theoretical value. Due primarily to the photoexcitation-induced small polarons (hereinafter referred to as polaron) in BiVO 4 , charge trapped by a deformed lattice limited charge transport, is insensitive to thermal activation under a certain temperature. , Furthermore, polarons created by oxygen vacancy can act as efficient recombination centers to quickly capture photogenerated electrons or holes and accelerate nonradiative charge recombination …”
mentioning
confidence: 99%